Capnocytophaga sputigena Causing Complicated Sinusitis With Intracranial Involvement in a Pediatric Patient - Karan Gandhi; Chloe Pulver; Lucas D. D. Foster; David Plemel; Nancy Nashid; Keng Tay; Julie E. Strychowsky (Case Reports in Otolaryngology)
This report presents a rare case of acute bacterial rhinosinusitis with orbital and intracranial complications caused by Capnocytophaga sputigena in a pediatric patient. A 15-year-old male presented with orbital cellulitis, acute sinusitis, and meningismus. Brain imaging showed evidence of early intracranial abscess formation and areas of cerebral infarction. He underwent urgent endoscopic sinus surgery (ESS) and drainage of an orbital subperiosteal abscess. This case underscores the critical role of timely diagnostic imaging, multidisciplinary care, appropriate surgical management, and effective culture-directed antimicrobial therapy in treating sinusitis and its complications.